High-precision geochronological constraints on the duration of 'Dinosaur Pompeii' and the Yixian Formation. Issue 6 (12th April 2021) - Zhong, Yuting; Huyskens, Magdalena H; Yin, Qing-Zhu; Wang, Yaqiong; Ma, Qiang; Xu, Yi-Gang
SUMMARY: High-precision U-Pb zircon ages of 125.755 ± 0.061 Ma and 124.122 ± 0.048 Ma, respectively, represent the onset and termination of Yixian Formation in the Jin-Yang basin, bracketing its duration to 1.633 ± 0.078 Myr.